Pengaruh Media Pembelajaran Berbasis Teknologi Informasi Dalam Proses Pembelajaran Kimia Terhadap Peningkatan Hasil Belajar Siswa - Nurchaili -- (Jurnal Pendidikan dan Kebudayaan, 2010)
The purpose of this study is to determine whether there is any effect of the using learning media based IT in the chemicals learning processs to the improvement of student learning outcomes. This study used quantitative explanation of experiment. The total samples of this research are 184 students which are grouped into experimental groups and control groups based on the pattern of the equivalent parallel groups. The instrument used is a matter of testing. The results were obtained an average rating of information technology-based chemistry learning outcomes of 89.06 with a standard deviation of 4.748, while the average value of learning outcomes in the conventional chemical is 62.05 with a standard deviation of 13.133. Both of the two groups average value was statistically tested using t statistics test on the significance test (Î± = 5%) to determine whethe there is a difference. From the test results obtained t value (18.552) is bigger than t table (1.986) with significance 0.000. So, it can be concluded both average learning outcomes differ significantly. It can be concluded that learning media based information technology (IT) can be used in the learning process, particularly chemicals, in order to improve student learning outcomes.